Antineoplastic Activity of New Transition Metal Complexes of 6-Methylpyridine-2-carbaldehyde-N(4)-ethylthiosemicarbazone: X-Ray Crystal Structures of [VO2(mpETSC)] and [Pt(mpETSC)Cl]. (25th May 2010) - Elsayed, Shadia A.; El-Hendawy, Ahmed M.; Mostafa, Sahar I.; Jean-Claude, Bertrand J.; Todorova, Margarita; Butler, Ian S.
Abstract : New complexes of dioxovanadium(V), zinc(II), ruthenium(II), palladium(II), and platinum(II) with 6-methylpyridine-2-carbaldehyde-N(4)-ethylthiosemicarbazone (HmpETSC) have been synthesized. The composition of these complexes is discussed on the basis of elemental analyses, IR, Raman, NMR (H 1, C 13, andP 31 ), and electronic spectral data. The X-ray crystal structures of [VO 2 (mpETSC)] and [Pt(mpETSC)Cl] are also reported. The HmpETSC and its [Zn(HmpETSC)Cl 2 ] and [Pd(mpETSC)Cl] complexes exhibit antineoplastic activity against colon cancer human cell lines (HCT 116).